Azar, influencia: sincronicidad analogías temáticas y estructurales entre tres obras de Berlioz, Víctor Hugo y Delacroix - García Álvarez, César (Estudios humanísticos. Geografía, historia y arte, 1999)
The analysis of three works of the Romantic French Art (the Symphonie Fantastique by Berlioz, Notre Dame de Paris, by Victor Hugo, and Liberty Leading the People, by Delacroix), shows and proves the existence of deep structural and thematical analogies in them. The coincidences in the conception of the Feminine and its relationship with the idea of artist are not anecdotal, and could be explained by different hypothesis. Firstly, as a result of conscious influences among the three artists. Secondly, as manifestations of the period's latent culture and, finally, as three formal mouldings of the anima archetype.